(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyse the influence of workload, work-related stress and work-life balance on employee performance at the Public Welfare Bureau of the Regional Secretariat of Southeast Sulawesi Province. The study employs a quantitative approach with an explanatory research design. The study population comprises all civil servants at the agency, totalling 45 individuals, with a census sampling technique used. Data were collected via a questionnaire and analysed using multiple linear regression. The results indicate that workload, work-related stress, and work-life balance simultaneously have a significant effect on employee performance. Partially, workload and work-related stress have a negative and significant effect on performance, suggesting that increased workload and work-related pressure tend to reduce employee performance. Conversely, work-life balance has a positive and significant effect on performance, suggesting that a balance between work demands and personal life plays a crucial role in enhancing employee performance. These findings underscore the importance of workload management, stress control, and the implementation of policies supporting work-life balance to improve employee performance within the government bureaucracy.